The implementation of policies and the impact of handling Covid-19 originating from the World Health Organization's Point of View - Pham Hoang (Borong Newinera Publisher, 2021)
The purpose of this article is to describe the capacity and role of WHO in dealing with the spread of COVID-19 and to discuss in-depth articles at the stages of policy implementation that specifically discuss the WHO protocol that is applied in dealing with the spread of Covid-19. The implementation of the policy to handle the spread of COVID-19 considers various aspects not only health but also the economic and social impacts resulting from government decision making. In addition, response measures are implemented through the Acceleration of COVID-19 Handling task which is part of the formation of structures, structure is one of the aspects that are considered in Edward III's implementation theory besides communication, resources and disposition because the presence of a structure helps implement policies has a significant effect. on policy implementation. The support of all elements of the government, the private sector in compliance with government and WHO instructions, especially regarding social distancing and physical distancing, will have a big impact in preventing the spread of COVID-19.